2019
DOI: 10.1038/s41598-018-37762-6
|View full text |Cite
|
Sign up to set email alerts
|

An Equation Based on Fuzzy Mathematics to Assess the Timing of Haemodialysis Initiation

Abstract: In order to develop an equation that integrates multiple clinical factors including signs and symptoms associated with uraemia to assess the initiation of dialysis, we conducted a retrospective cohort study including 25 haemodialysis centres in Mainland China. Patients with ESRD (n = 1281) who commenced haemodialysis from 2008 to 2011 were enrolled in the development cohort, whereas 504 patients who began haemodialysis between 2012 and 2013 were enrolled in the validation cohort comprised. An artificial neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Chang et al [ 14 ] quantified uremic burden based on 7 uremic indicators that reached the predefined threshold (hemoglobin, serum albumin, blood urea nitrogen, serum creatinine, potassium, phosphorus, and bicarbonate); dialysis timing was classified as standard (met 0–2 uremic indicators), late (3–5indicators), and very late (6–7 indicators); and no correlation was found between late or very late group and mortality. Ying et al [ 26 ] developed an equation based on fuzzy mathematics to assess the timing of haemodialysis initiation, the results showed that the combination of sex, age, serum creatinine, blood urea nitrogen, serum albumin, haemoglobin, serum phosphorus, diabetes mellitus, and heart failure as equation variables resulted in the best accuracy to prognose 3-year survival. Matthew et al [ 19 ] categorized clinically documented primary indication for dialysis initiation into 4 groups: laboratory evidence of kidney function decline (reference category), uremic symptoms, volume overload or hypertension, and other/unknown; and found that volume overload or hypertension was associated with the highest risk for subsequent mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al [ 14 ] quantified uremic burden based on 7 uremic indicators that reached the predefined threshold (hemoglobin, serum albumin, blood urea nitrogen, serum creatinine, potassium, phosphorus, and bicarbonate); dialysis timing was classified as standard (met 0–2 uremic indicators), late (3–5indicators), and very late (6–7 indicators); and no correlation was found between late or very late group and mortality. Ying et al [ 26 ] developed an equation based on fuzzy mathematics to assess the timing of haemodialysis initiation, the results showed that the combination of sex, age, serum creatinine, blood urea nitrogen, serum albumin, haemoglobin, serum phosphorus, diabetes mellitus, and heart failure as equation variables resulted in the best accuracy to prognose 3-year survival. Matthew et al [ 19 ] categorized clinically documented primary indication for dialysis initiation into 4 groups: laboratory evidence of kidney function decline (reference category), uremic symptoms, volume overload or hypertension, and other/unknown; and found that volume overload or hypertension was associated with the highest risk for subsequent mortality.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted this population-based multicentre retrospective cohort study from the database of Dialysis Initiation based on Fuzzy mathematics Equation study (DIFE),14 which focuses on adults patients with ESKD undergoing maintenance haemodialysis in China and aims to establish a novel equation of timing of haemodialysis initiation based on a fuzzy mathematical method 15 16…”
Section: Methodsmentioning
confidence: 99%
“…The sample size estimate is mainly based on the primary endpoint of the 3-year all-cause mortality from the previous retrospective cohort DIFE study, which showed that the 3-year mortality of the optimal start dialysis group was 8.38% and that of the late start dialysis group was 19.4% 21. Using PASS V.15 of the Power and Sample Size Calculation program (NCSS, LLC), we estimated a sample size of 154 per group (assuming a type I error rate of 5% with 80% power, two-sided test, with p<0.05 considered statistically significant).…”
Section: Methods and Analysismentioning
confidence: 99%
“…The DIFE study showed that the 3-year dialysis mortality of patients in the optimal start dialysis group (DIFE value of 30 to 35) was markedly lower (8.38%) than the late-start dialysis group (DIFE value less than 30) of 19.4%. Moreover, receiver operating characteristic curve analysis indicated that the area under the curve for the prediction of a 3-year death during dialysis initiation assessed by the DIFE was significantly higher than that predicted by eGFR (0.70 vs 0.55, p<0.01) 21. Therefore, the DIFE is more accurate and effective to assess the timing of haemodialysis initiation than eGFR alone.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation